La démocratie au concret : Les enjeux politiques et territoriaux de la mise en place du Budget Participatif dans la Tunisie post-Ben Ali (2011-2016) - Joseph-Désiré Som-1; Damiano De Facci (L’Année du Maghreb)
The Participatory budgeting is a modality of local democracy, a guarantee of better citizen participation in the co-production of local public action. Its use seems to have achieved some success in some ten Tunisian communes since 2014, to the point that the will of several state and associative actors to institutionalize it nationally. The promotion of participatory mechanisms at the local level is far from being a «new idea» in Tunisia and was once in the service of a project to legitimize the regime and control of proximity of citizens. But in its new implementation, without completely breaking with the old logics, it allows to identify some of the territorial and political dynamics that shape the process of decentralization in post-Ben Ali Tunisia. From an input by policy transfers, we show that the participatory budget is the result of a combinatorial approach. On the one hand, it is the product of the encounter between circular arenas of participation and local entrepreneurs in the voluntary sector; On the other, it is at the heart of stakes and political struggles territorially located. It is also a space for the enunciation of a new relationship with the political, it is also for several local actors, in particular municipal executives in need of legitimacy, an opportunity to build political capital and a modality for framing popular dynamics.